Model Pembelajaran Portofolio dalam Pembelajararan Tematik Terpadu - Ulfah Elkhaira; Reinita Reinita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to describe the improvement of learning outcomes by using the Portfolio model in integrated thematic learning of fifth grade. In the implementation the teacher has not used a learning model that can arouse students' enthusiasm, and does not provide problems in learning and student work outcomes are not kept together so it is difficult to see student development. This type of research is Classroom Action Research and uses qualitative and quantitative approaches. The subject of this research is the fifth grade elementary school students. The data of this study are the results of observations and tests of each learning improvement action by applying the portfolio model. This portfolio model has 6 stages namely